A Novel Method of Color Appearance Simulation Using Achromatic Point Locus With Lightness Dependence. (March 2018) - Kuriki, Ichiro
The purpose of the present study is to propose a simple algorithm for color appearance simulation under a color illuminant. Achromatic point is a chromaticity of rays that appear neither red nor green, neither blue nor yellow under a given illuminant condition. Saturation and hue of surface colors are evaluated with respect to the achromatic point of the same lightness, while the achromatic point under a colored illuminant depends on the lightness tested. We previously found that this achromatic point locus can be simply approximated as a line with a parallel offset from the lightness axis of CIE LAB space normalized to daylight. We propose a model that applies shifts in the lightness direction after applying hue/saturation shifts using the cone-response (von Kries) transformation under an iso-lightness constraint, such that achromatic points would be aligned with the lightness axis in the CIE LAB space under daylight normalization. We tested this algorithm, which incorporates evaluation of color appearance in different lightness levels, using #theDress image. Resemblance between our simulation and subjective color-matching results implies that human color vision possibly processes shifts in color and lightness independently, as a previous study reported. Changes in the chromaticity distribution of the images were compared with conventional models, and the proposed model preserved relative color difference better, especially at the lower lightness levels. The better performance in lower lightness levels would be advantageous in displays with wider dynamic range in luminance. This implies that the proposed model is effective in simulating color appearance of images with nonnegligible lightness and color differences.